2015
DOI: 10.1186/s40659-015-0027-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbamazepine and gabapentin on excitability in the trigeminal subnucleus caudalis of neonatal rats using a voltage-sensitive dye imaging technique

Abstract: BackgroundThe antiepileptic drugs carbamazepine and gabapentin are effective in treating neuropathic pain and trigeminal neuralgia. In the present study, to analyze the effects of carbamazepine and gabapentin on neuronal excitation in the spinal trigeminal subnucleus caudalis (Sp5c) in the medulla oblongata, we recorded temporal changes in nociceptive afferent activity in the Sp5c of trigeminal nerve-attached brainstem slices of neonatal rats using a voltage-sensitive dye imaging technique.ResultsElectrical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It is noteworthy to mention that GBP inhibited PKC signaling pathways [48][49][50][51][52]. Gabapentin also inhibited the spinal neuronal action of NMDA receptors [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy to mention that GBP inhibited PKC signaling pathways [48][49][50][51][52]. Gabapentin also inhibited the spinal neuronal action of NMDA receptors [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that opioid treatment altered the expression of the NMDA receptor in the hypothalamus [57,58] and NMDA receptor antagonist and intrathecal gabapentin inhibited the morphine induced development of spinal tolerance and dependence [59,60]. Recent evidences demonstrated that gabapentin inhibited the spinal neuronal action of NMDA receptors [53][54][55]. It was postulated that the spinal NMDA receptors antagonism by GBP might have played a role in blocking morphine tolerance and enhance morphine analgesia, the interference of its supra-spinal circuits is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of interaction of carbamazepine with the glutamatergic system are not fully understood. Some studies have found that carbamazepine affects the signalling pathways that involve NMDARs [225,226,227]. This data does not exclude the fact that carbamazepine can interact directly with NMDARs.…”
Section: Psychotropic Drugs For Management Of Pain and Itching Synmentioning
confidence: 95%
“…In the peripheral nervous system, these targeted sodium channels are predominantly expressed on sensory neurons and result in limited firing rates of those neurons . Past research has implicated carbamazepine as also affecting calcium channels, as well as NMDA receptors, though effects were observed at concentrations well above therapeutic levels and above the known carbamazepine toxicity limit of 63 μmol/L. Though numerous studies have been performed regarding the mechanism of action of carbamazepine, such as modulated activity of a transiently expressed single isoform of GABAA receptor, the primary mechanism appears to be restricting neuronal firing rates via limiting activity of selective sodium channels.…”
Section: Introductionmentioning
confidence: 99%